Implementasi Strategi Pembelajaran Guru PJOK pada Kurikulum Nasional di SMP Negeri 3 Palu - Suryani Suryani; Kamarudin Kamarudin; Hendra Iskandar; Muh. Saldi (Universitas Hamzanwadi, 2026)
This study was motivated by the still-low level of understanding among Physical Education (PJOK) teachers regarding the implementation of a competency-based curriculum, as well as the limited number of specific studies on PJOK teaching strategies within the context of the National Curriculum. The study aims to describe the implementation of teaching strategies by PJOK teachers under the National Curriculum at SMP Negeri 3 Palu. The method used was descriptive quantitative research with a cross-sectional survey design. The sample consisted of 4 Physical Education teachers selected through total sampling. Data were collected using a questionnaire comprising 20 items on a 4-point Likert scale covering six indicators, supplemented by observations and documentation. The instrument was validated by three experts with a CVI of 0.89 and a Cronbach’s Alpha reliability of 0.87. Data analysis employed descriptive percentage calculations. The results showed that the implementation of Physical Education learning strategies reached 84.06% (Very Good). Instructional planning achieved the highest score (90.63%), followed by the use of media (87.50%), the implementation of deep learning and differentiation (85.94%), competency-based assessment (82.81%), and support and training (81.25%), while implementation constraints scored the lowest (72.92%). The study concluded that Physical Education teachers have implemented learning strategies in accordance with the National Curriculum; however, improvements in facilities and teacher competencies through ongoing training are still needed.